2011
DOI: 10.3382/ps.2011-01511
|View full text |Cite
|
Sign up to set email alerts
|

Effects of copper-loaded chitosan nanoparticles on growth and immunity in broilers

Abstract: Effects of dietary copper-loaded chitosan nanoparticle (CNP-Cu) supplementation on growth performance, hematological and immunological characteristics, and the cecal microbiota in broilers were investigated. Three hundred healthy Avian × Avian (1-d-old) broilers were randomly assigned into 5 dietary groups (20 birds per replicate with 3 replicates per group). Birds were fed with 0 (the control group), 50, 100, 150 mg/kg of CNP-Cu and 50 mg/kg chlorotetracycline (CTC, a positive control group) for 42 d. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
29
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(39 citation statements)
references
References 30 publications
7
29
0
1
Order By: Relevance
“…This is consistent with results reported by Wang et al . (), who found that administration of nano‐Cu to chickens with chitosan in the amounts of 50, 100, 150 mg/kg of feed caused an increase in the level of IgA, IgM and IgG as well as complements C3 and C4 in the blood. Another experiment (Pineda et al .…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with results reported by Wang et al . (), who found that administration of nano‐Cu to chickens with chitosan in the amounts of 50, 100, 150 mg/kg of feed caused an increase in the level of IgA, IgM and IgG as well as complements C3 and C4 in the blood. Another experiment (Pineda et al .…”
Section: Discussionmentioning
confidence: 99%
“…Both copper sources significantly reduce the incidences of diarrhoea compared to the control fed pigs. In study P116(Wang et al, 2011), significantly lower diarrhea incidence was observed in piglets fed a diet supplemented with 1.5 mg/kg Cu as Cu-Chitosan nanoparticles compared to the control fed piglets. However, although numerical lower, the incidence of diarrhoea was not significantly lower than in piglets fed copper free Chitosan nanoparticles.…”
mentioning
confidence: 89%
“…Also, Lien (2009) found that the bioavailability of copper improved in pigs fed diets supplemented with 50 mg Nano-Cu/kg diet. In broilers, Wang et al (2011) showed that supplementation of Nano-Cu at level of 50 or 100 mg/kg diet improves growth performance, strengthen the immune system, enhance protein synthesis and activates the cecal microbiota. Studies so far have indicated that the application of nano minerals in animal production and immunity is promising.…”
mentioning
confidence: 99%